Hot topics in allergen immunotherapy, 2023: Current status and future perspective - Zemelka‐Wiacek, Magdalena; Agache, Ioana; Akdis, Cezmi A.; Akdis, Mübeccel; Casale, Thomas B.; Dramburg, Stephanie; Jahnz‐Różyk, Karina; Kosowska, Anna; Matricardi, Paolo M.; Pfaar, Oliver; Shamji, Mohamed H.; Jutel, Marek (Allergy (Copenhagen), 2024)
The importance of allergen immunotherapy (AIT) is multifaceted, encompassing both clinical and quality‐of‐life improvements and cost‐effectiveness in the long term. Key mechanisms of allergen tolerance induced by AIT include changes in memory type allergen‐specific T‐ and B‐cell responses towards a regulatory phenotype with decreased Type 2 responses, suppression of allergen‐specific IgE and increased IgG1 and IgG4, decreased mast cell and eosinophil numbers in allergic tissues and increased activation thresholds. The potential of novel patient enrolment strategies for AIT is taking into account recent advances in biomarkers discoveries, molecular allergy diagnostics and mobile health applications contributing to a personalized approach enhancement that can increase AIT efficacy and compliance. Artificial intelligence can help manage and interpret complex and heterogeneous data, including big data from omics and non‐omics research, potentially predict disease subtypes, identify biomarkers and monitor patient responses to AIT. Novel AIT preparations, such as synthetic compounds, innovative carrier systems and adjuvants, are also of great promise. Advances in clinical trial models, including adaptive, complex and hybrid designs as well as real‐world evidence, allow more flexibility and cost reduction. The analyses of AIT cost‐effectiveness show a clear long‐term advantage compared to pharmacotherapy. Important research questions, such as defining clinical endpoints, biomarkers of patient selection and efficacy, mechanisms and the modulation of the placebo effect and alternatives to conventional field trials, including allergen exposure chamber studies are still to be elucidated. This review demonstrates that AIT is still in its growth phase and shows immense development prospects.